Naomi Mengeluh atau Menggugat Allah atas Peristiwa Kehilangan?: Suatu Tafsiran terhadap Narasi Rut 1:1-22 - Vani Mega Rianna Mantong Tendenan (KENOSIS: Jurnal Kajian Teologi, 2021)
Naomi experiences the loss of her husband and two children is the opening narrative of the book of Ruth. Naomi's loss becomes an experience of faith that drives the narrative of the book of Ruth. This paper aims to eliminate the loss in the perspective of the book of Ruth specifically based on Ruth 1:1-22 by using the exegesis method that pays attention to the context, genre, and content of the text. The stages carried out are the first to explain the exegesis method, namely narrative, the second is to describe the context, the third is to analyze the genre of the book of Ruth, and the fourth is to analyze the words wattissaer, noomi, and mara. Then fifth notice the text of Ruth 1:1-22. Based on the research results on the text of Ruth 1:1-22, the authors found the word wattissaer as an indication of the cause of the emergence of the name game from Naomi from the word noomi to mara. The historical context, authorship, and theological context of the book of Ruth show the loss of Naomi as part of the experience of faith to see God's role in it. Wordplay becomes possible in the book of Ruth because its genre as a story or narrative also supports the narrator in doing so. The author sees the loss experienced by Naomi as not an ordinary loss but a loss that can be understood as part of God's test of Naomi's faith, which then changes Naomi's name to respond to complaints to God but not to suing God.Â AbstrakNaomi mengalami peristiwa kehilangan suami serta kedua anaknya yang merupakan narasi pembuka Kitab Rut. Kehilangan yang dialami Naomi menjadi pengalaman iman yang menggerakkan narasi Kitab Rut. Tulisan ini bertujuan untuk mengkaji kehilangan dalam perspektif kitab Rut secara khusus berdasar pada Rut 1:1-22 dengan menggunakan metode eksegesis yang memperhatikan konteks, genre, dan isi teks. Adapun tahap-tahap yang dilakukan ialah pertama penjelasan metode eksegesis yaitu naratif, kedua penjabaran konteks, ketiga menganalisis genre dari kitab Rut, keempat analisa terhadap kata wattissaer, noomi, dan mara. Kemudian kelima menafsirkan teks Rut 1:1-22. Berdasarkan pada hasil penelitian terhadap teks Rut 1:1-22, penulis menemukan kata wattissaer sebagai indikasi penyebab munculnya permainan nama dari Naomi dari kata noomi menjadi mara. Konteks sejarah, kepenulisan dan konteks teologis kitab Rut menunjukkan peristiwa kehilangan Naomi sebagai bagian dari pengalaman iman untuk melihat peran Allah di dalamnya. Permainan kata menjadi sangat mungkin dalam kitab Rut karena genrenya sebagai cerita atau narasi juga mendukung narator dalam melakukannya. Penulis melihat kehilangan yang dialami Naomi bukanlah kehilangan biasa melainkan kehilangan yang dapat dipahami sebagai bagian dari ujian Allah terhadap iman Naomi yang kemudian perubahan nama Naomi menjadi respons keluhan kepada Allah tetapi bukan menggugat Allah.Â